Safe Food, Fair Food: Participatory risk analysis for improving the safety of informally produced and marketed food in sub-Saharan Africa - Grace, Delia; Makita, K.; Kang'ethe, Erastus K.; Bonfoh, Bassirou (2010)
Millions of small-scale farmers efficiently supply the great majority of the meat and milk market in Africa. Surging demand for livestock products (the “livestock revolution”) is an unprecedented opportunity for setting poor farmers on pathways out of poverty, but to gain maximum benefit they must be able to produce safe food of acceptable quality. Currently, most smallholder livestock products are sold in informal markets where conventional regulation and inspection methods have failed and where private or civil sector alternatives have not emerged: as a consequence, most livestock-derived food products contain high levels of hazards. Quantitative risk-based approaches for assessing and managing food safety offer a powerful new method for reducing the enormous health burden imposed by food borne disease, while taking into account other societal goals such as pro-poor growth. However, application to food safety problems in Africa has been limited. We discuss some of the constraints and a new approach which can help overcome these: Participatory Risk Analysis, and give examples of its current application in west, east and south Africa.